2014
DOI: 10.1016/j.fgb.2014.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and enzyme production of Trichoderma reesei Rut C-30 are affected by the physical and structural characteristics of cellulosic substrates

Abstract: The industrial production of cellulolytic enzymes is dominated by the filamentous fungus Trichoderma reesei (anamorph of Hypocrea jecorina). In order to develop optimal enzymatic cocktail, it is of importance to understand the natural regulation of the enzyme profile as response to the growth substrate. The influence of the complexity of cellulose on enzyme production by the microorganisms is not understood. In the present study we attempted to understand how different physical and structural properties of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 39 publications
4
46
0
Order By: Relevance
“…In a previous study by our group, enzyme production during the filamentous fungus T. reesei growth on cellulose-rich pulps isolated from softwood and NCC-OPHS-ND was compared with growth of the fungus on Avicel. It was found that enzyme production by the filamentous fungus T. reesei showed the highest protein production when Avicel was used as a carbon and energy source for the fungus and that protein production levels were significantly lower when cellulose-rich pulps or NCC-OPHS-ND were used as carbon sources [ 36 ]. This observation led us to hypothesize that there may exist a relation between the structural properties of the substrate used for the fungal growth and the capacity of the produced enzymes to hydrolyse the same substrate.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study by our group, enzyme production during the filamentous fungus T. reesei growth on cellulose-rich pulps isolated from softwood and NCC-OPHS-ND was compared with growth of the fungus on Avicel. It was found that enzyme production by the filamentous fungus T. reesei showed the highest protein production when Avicel was used as a carbon and energy source for the fungus and that protein production levels were significantly lower when cellulose-rich pulps or NCC-OPHS-ND were used as carbon sources [ 36 ]. This observation led us to hypothesize that there may exist a relation between the structural properties of the substrate used for the fungal growth and the capacity of the produced enzymes to hydrolyse the same substrate.…”
Section: Resultsmentioning
confidence: 99%
“…The assay was performed in 96-well microtitre plates in duplicates for each sample. The protein concentration was defined as the amount of extracellular proteins measured per L of fungal supernatant515253. All analyses were done in triplicate in a temperature-controlled incubator.…”
Section: Methodsmentioning
confidence: 99%
“…The Fibres were stored in the never-dried state at 4°C until use. AT fibre was produced from the Fibre, according to the procedure described previously by prolonged hydrolysis with hydrochloric acid at elevated temperature (95-100°C) for 17 h (Peciulyte et al 2014), and stored in excess deionized water in a glass bottle with a lid at room temperature. Avicel Ò PH-101 was purchased as a powdered microcrystalline cellulose (Fluka BioChemika, Ireland).…”
Section: Cellulosic Substratesmentioning
confidence: 99%